Ideology Strengthening Strategy Muhammadiyah Cadres In The Era of Disruption - Wisono, Dody; Romelah, Romelah; Nurhakim, Moh (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2023)
Muhammadiyah as a parchment movement cannot be separated from social problems arising from changing times, such as individuality, declining spirituality, the emergence of hedonism and pragmatism, as well as ideological variants in Muhammadiyah cadres. Therefore, to maintain the existence and authenticity of the values of the Muhammadiyah struggle, it is necessary to strengthen the ideology of the community cadre. This research uses a descriptive type of research with a qualitative approach. The method used is library research. Where the data sources studied come from libraries or documentation, namely from various book literature, journal articles, or national and international scientific publications related to the theme of discussion. Meanwhile, to carry out data analysis, the authors used Milles and Huberman's guidelines including data collection, data reduction, and conclusion. Substantively Muhammadiyah ideology can be known through the muqaddimah of the articles of association of Muhammdiyah, Matan beliefs and ideals of Muhammadiyah life, and Muhammadiyah personality. Efforts that Muhammadiyah can make in strengthening ideology to community cadres include: first, through the Mubaligh Muhammadiyah school; Second, through the optimization of Baitul Arqam Muhammadiyah; Third, optimization of the Muhammadiyah recitation curriculum; fourth, through the role of the family; and Fifth, grounding digital proselytizing.